2013
DOI: 10.1177/2048872613516018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osmolality predicts clinical outcome in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Using the 4th quartile of plasma osmolality at admission as a natural cut-off point, osmolality in Q4, as compared to Q1-3, was significantly predictive of short term but not long-term outcome in ACS patients undergoing coronary stenting. Our data suggest osmolality to be an independent, feasible, and cost-effective tool for rapid risk stratification in ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
3
38
2
Order By: Relevance
“…Bhalla et al [14] found an association between increased osmolality and short-term mortality in 167 consecutive patients with acute stroke. Recently, two studies showed an association of increased sOsmo and short- as well as long-term mortality in patients after ACS [3, 15]. Rohla et al [3] analyzed the data of 985 consecutive patients with non-STEMI and STEMI in whom sOsmo was calculated from laboratory results obtained within 8 h of admission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bhalla et al [14] found an association between increased osmolality and short-term mortality in 167 consecutive patients with acute stroke. Recently, two studies showed an association of increased sOsmo and short- as well as long-term mortality in patients after ACS [3, 15]. Rohla et al [3] analyzed the data of 985 consecutive patients with non-STEMI and STEMI in whom sOsmo was calculated from laboratory results obtained within 8 h of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies showed an association of increased sOsmo and short- as well as long-term mortality in patients after ACS [3, 15]. Rohla et al [3] analyzed the data of 985 consecutive patients with non-STEMI and STEMI in whom sOsmo was calculated from laboratory results obtained within 8 h of admission. Patients in the highest sOsmo quartile had the highest risk of 30-day mortality compared to patients in the other quartiles combined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computable osmolarity, including these components, is an important indicator for CAD and mortality [17] Hyperosmolar nutrition, termed sodium, glucose and protein-rich nutrition, is the basis for atherosclerosis, leading to metabolic activity resulting in increased heat, especially coronary artery deterioration in the body6. It is important to remove the person's hyperosmolar from the diet or to define the limits, to protect from the CAD, at least to delay disease development.…”
Section: Discussionmentioning
confidence: 99%